Developing Critical Thinking in the Next Generation of Teachers at Universities: - Erika Novotna (Ignatianum University Press, 2021)
The world of education has changed. Information is available anywhere and at any time. It can be daunting to understand and assess it and to distinguish a hoax from objective reality. The training of future teachers at universities needs to be changed so that a graduate from a Faculty of Education will become a professional capable of teaching others how to learn. Teachers can no longer only transmit information and evaluate how students acquire it. They should make learning meaningful and guide learners toward critical thinking. The underlying assumption is that they themselves can think critically. The aim of the study is to compare the level of critical thinking in university students between two generations of students, Generation Y (Millennials) and Generation Z (the iGeneration).